Optimal Minimal-Perturbation University Scheduling With Faculty Preferences - Kotas, Jakob; Pham, Peter; Koellmann, Sam (The PUMP Journal of Undergraduate Research, 2022)
In the university scheduling problem, sometimes additions or cancellations of sections of a course occur shortly before the beginning of the academic term, necessitating last-minute teaching staffing changes. We present a decision-making framework that both minimizes the number of course swaps, which are inconvenient for instructors, and maximizes instructors' preferences for section times they wish to teach. The model is formulated as an integer linear program (ILP). Numerical simulations for a hypothetical mid-sized academic department are presented.